Nitrogen utilization analysis reveals the synergetic effect of arginine and urea in promoting fucoxanthin biosynthesis in the mixotrophic marine diatom Phaeodactylum tricornutum - Yang, Runqing; Wei, Dong; Pohnert, Georg (Frontiers in Marine Science, 2022)
Fucoxanthin is a new dietary ingredient applied in healthy foods with specific benefits of body weight loss and liver fat reduction. The marine diatom Phaeodactylum tricornutum is a highly suitable species for fucoxanthin production. In the present study, aiming to promote fucoxanthin biosynthesis in mixotrophic P. tricornutum, NaNO3, tryptone, and urea were evaluated as nitrogen sources with 0.10 mol L−1 of glycerol as the organic carbon source for mixotrophic growth in shake flasks. Compared to NaNO3, the mixture of tryptone and urea (referred to as T+U, 1:1, mol N:mol N) as organic nitrogen sources could induce a higher biomass and fucoxanthin production. Through nitrogen utilization analysis, leucine, arginine, lysine, and phenylalanine in the T+U medium were identified as the amino acids that primarily support cell growth. Among those amino acids, arginine causes the highest rate of nitrogen utilization and cell growth promotion. After 12 days of cultivation, the highest biomass concentration (3.18 g L−1), fucoxanthin content (12.17 mg g−1), and productivity (2.68 mg L−1 day−1) were achieved using 25 mmol N L−1 of arginine and 5 mmol N L−1 of urea as nitrogen sources, indicating that arginine and urea performed synergistically on enhancing biomass and pigment production. This study provides new insights into the promotion of fucoxanthin biosynthesis by nitrogen utilization analysis and verifies the synergetic effect of arginine and urea on facilitating the development of a promising strategy for efficient enhancement of fucoxanthin production through mixotrophic cultivation of P. tricornutum.